Bactrocera fly infestation on starfruit, Averrhoa carambola L. in Selangor, Malaysia and its parasitoids - Juma, Salim Ali (2015)
Tephritid fruit flies, Bactrocera carambolae (Drew and Hancock), and B. papayae (Drew and Hancock), belong to the Bactrocera dorsalis complex are key pests of valuable fruits in Southeast Asia. Control of these pests is often limited by difficulties in their identification that have been increasing due to recent occurrences of species with morphological characteristics of both B. carambolae and B. papayae (hereafter known as intermediates). Opiinae parasitoids (Hymenoptera: Braconidae) are the important biological control agents of fruit flies in IPM. Therefore, a study was conducted to investigate the occurrence of intermediates and its proportion from their parental stocks based on field collection of flies infested starfruits, Averrhoa carambola L. and methyl eugenol-baited traps in three locations. In addition, field infestation of Bactrocera fruit flies and the associated Opiinae parasitism was assessed using infested fruits. Moreover, population fluctuation of Bactrocera fruit flies was studied using methyl eugenol trapping in UPM and Semenyih. A total of 7,144 fruit flies composed of B. carambolae (59%), B. papayae (16%) and intermediates (25%) were collected from 240 infested fruits. From set traps, 12,522 male flies of B. carambolae (21%), B. papayae (16%) and intermediates (63%) were collected. Nearly, all collected fruits were infested by Bactrocera fruit flies and the mean number of pupae per fruit respectively from UPM, DOA and Semenyih were 49, 47 and 28. However, per weight (g) of fruit the infestation was 0.65, 0.88 and 0.45. Similarly, the mean number of adult fruit flies per fruit was 34, 39 and 16 respectively. Opiinae parasitoids of four species; Fopius arisanus Sonum, Diachasmimorpha longicaudata Ashmead, Psyttalia fletcheri Silvesteri and Psyttalia incisi Silvesteri were identified and the percentage of parasitism were in the order of Semenyih > UPM > DOA at values of 33%, 24% and 9% respectively.The contribution of F. arisanus was more than 70% of total parasitoids while of others was nearly similar. The population of B. carambolae was significantly higher (P < 0.05) in UPM while B. papayae was significantly higher (P < 0.05) in Semenyih. The population of intermediates was not significantly different (P > 0.05) between the locations similar to that of total flies. Among sampling months, populations showed nearly similar fluctuation trends with peak in October, December and January in UPM. However, in Semenyih steady population throughout the year was observed with fluctuation for some fly species. The population of fruit flies in UPM was highly correlated with rainfall season though; B. papayae was also correlated with temperature. In Semenyih, populations of intermediates and total flies were correlated with relative humidity. Similarly, the stepwise regression analysis result from UPM showed that rainfall contributes significantly on population variations of fruit flies, except for B. papayae. In Semenyih, only relative humidity contributed significantly to population variations of intermediates (R2 = 0.49) and total fruit flies (R2 = -0.37). For the population dispersion, values of various indices and regression models in all sampling months for examined species indicated aggregated distribution except for few cases in Semenyih. The results suggest the existence of intermediate species of damaging B. dorsalis species and their parasitoids in studied areas. The relatively difference among locations in flies infestation and Opiinae parasitism is mostly related to orchard management and host conditions. However, population of fruit flies is highly influenced by weather condition.